Passive and active network analysis and synthesis. - Budak, Aram. ([S.l.] : Houghton Mifflin School, 1974)
The material in this comprehensive volume was selected to provide physical insight and thorough understanding of the complex-frequency domain and its application to circuits. Well-organized, self-contained chapters detail analysis and synthesis for passive as well as active networks, present and compare a variety of approximating functions, and emphasize the study of widely used second-order functions and their realizations. Multiple examples designed to facilitate learning and outline the necessary theoretical perspectives and physical concepts for an open-ended approach to physical circuit design are provided.